Location and allocation: Inequity of access to liver transplantation for patients with severe acute‐on‐chronic liver failure in Europe. Issue 9 (16th June 2022) - Artzner, Thierry; Bernal, William; Belli, Luca S.; Conti, Sara; Cortesi, Paolo A.; Sacleux, Sophie‐Caroline; Pageaux, George‐Philippe; Radenne, Sylvie; Trebicka, Jonel; Fernandez, Javier; Perricone, Giovanni; Piano, Salvatore; et al.
Abstract: There is growing evidence that liver transplantation (LT) is the most effective treatment for acute‐on‐chronic liver failure grade‐3 (ACLF‐3). This study examines whether and how this evidence translates into practice by analyzing the variability in intensive care unit (ICU) admissions, listing strategies, and LT activity for patients with ACLF‐3 across transplantation centers in Europe. Consecutive patients who were admitted to the ICU with ACLF‐3, whether or not they were listed and/or transplanted with ACLF‐3, between 2018 and 2019 were included across 20 transplantation centers. A total of 351 patients with ACLF‐3 were included: 33 had been listed prior to developing ACLF‐3 and 318 had not been listed at the time of admission to the ICU. There was no correlation between the number of unlisted patients with ACLF‐3 admitted to the ICU and the number listed or transplanted while in ACLF‐3 across centers. By contrast, there was a correlation between the number of patients listed and the number transplanted while in ACLF‐3. About 21% of patients who were listed while in ACLF‐3 died on the waiting list or were delisted. The percentage of LT for patients with ACLF‐3 varied from 0% to 29% for those transplanted with decompensated cirrhosis across centers (average = 8%), with an I 2 index of 68% (95% confidence interval, 49%–80%), showing substantial heterogeneity among centers. The 1‐year survival for all patients with ACLF‐3 was significantly higher in centers that listed and transplanted more patients with ACLF‐3 (>10 patients) than in centers that listed and transplanted fewer: 36% versus 20%, respectively ( p  = 0.012). Patients with ACLF‐3 face inequity of access to LT across Europe. Waitlisting strategies for patients with ACLF‐3 influence their access to LT and, ultimately, their survival.